Case report: A de novo variant of CRMP1 in an individual with a neurodevelopmental disorder - Liu, Juan; Wang, Qi; Chen, Jia (Frontiers in Neuroscience, 2024)
BackgroundCRMP1 is a key protein involved in brain development.MethodsWe performed genetic testing through whole-exome sequencing (WES) in an individual with a neurodevelopmental disorder.ResultsWe identified a de novo heterozygous CRMP1 NM_001014809.3:c.1755del (p.Lys586fs) variant in the affected individual. This mutation was submitted to ClinVar (SCV005196589).ConclusionCurrently, the CRMP1 gene has no clear disease phenotype association in the Online Mendelian Inheritance in Man (OMIM) database. Our report may provide evidence for an association between the CRMP1 gene and neurodevelopmental disorders (NDDs).